2016
DOI: 10.18632/oncotarget.13214
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of Lgr5 and CXCR4 characterizes cancer stem-like cells of colorectal cancer

Abstract: Therapies designed to target cancer stem cells (CSCs) in colorectal cancer (CRC) may improve treatment outcomes. Different markers have been used to identify CSCs or CSC-like cells in CRC, but the enrichment of CSCs using these markers has yet to be optimized. We recently reported the importance of Lgr5-positive CRC cells in cancer growth. Here, we studied the possibility of using Lgr5 and CXCR4 as CSC markers for CRC. We detected high Lgr5 and CXCR4 levels in stage IV CRC specimens. Both high Lgr5 and CXCR4 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 48 publications
(41 reference statements)
3
26
0
Order By: Relevance
“…We have also found that grading scores of LGR5 and ALDH1 positive cells in the cancerous epithelium were significantly increased in CRC patients with advanced TNM stages than those with early stages. Those observations are consist with other groups’ findings [ 15 , 26 32 ], and imply that increased stem-like cell density might be the potential predicators for disease stage progression in both the adenoma and CRC. Mesenchymal stem like cell can be observed in the tumor stroma, it plays a critical role in remodeling tumor stroma and forming a supportive environment for cancer growth and metastasis [ 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…We have also found that grading scores of LGR5 and ALDH1 positive cells in the cancerous epithelium were significantly increased in CRC patients with advanced TNM stages than those with early stages. Those observations are consist with other groups’ findings [ 15 , 26 32 ], and imply that increased stem-like cell density might be the potential predicators for disease stage progression in both the adenoma and CRC. Mesenchymal stem like cell can be observed in the tumor stroma, it plays a critical role in remodeling tumor stroma and forming a supportive environment for cancer growth and metastasis [ 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…Lgr-5 plays an active role in pathogenesis of colorectal cancer [ 43 ], and the Lgr5 expression is closely related to tumorigenesis, 5-fluorouracil resistance and recurrence of colorectal cancer [ 43 , 44 ]. In stage IV colorectal cancer, high Lgr5 expression is associated with poor prognosis [ 45 ]. Therefore, Lgr5 is considered an indicator of poor prognosis and a potential target of colorectal cancer.…”
Section: Colorectal Cancer Stem Cellsmentioning
confidence: 99%
“…It is a downstream target gene of the Wnt/β-catenin signaling pathway and plays an important role in the embryonic development and organogenesis [ 1 , 2 ]. Recently, some studies show that Lgr5 is a marker of stem cells in small intestine and colon [ 3 ] and cancer stem-like cells of colorectal carcinoma (CRC) [ 4 ], and its over-expression is also detectable in CRC. Although R-spondin has been confirmed as a ligand of Lgr5 [ 5 ], the intracellular signaling pathway related to Lgr5 is still unclear, and the correlation of Lgr5 with the occurrence, maintenance and metastasis of CRC is also poorly understood.…”
Section: Introductionmentioning
confidence: 99%